Analysis of Water Resources Management Using The Dpsir Framework: Driver Pressure State Impact Response for River Water Pollution in Cilamaya Watershed - Laela Sulastri, Wini; Sudradjat, Arief (Green Publisher, 2024)
The availability of water in adequate quality is a crucial requirement for achieving various aspects of life, including human health, ecosystem, economy, social and environmental sustainability. This study analyzes the impact of land cover changes on water quality in the Cilamaya Watershed (DAS Cilamaya) using Qual2Kw and GIS modeling for the 2019-2023 period. The Cilamaya Watershed is closely related to the development of the north coast (Pantura Route), and the increasing number of development activities that have resulted in the increasingly concerning condition of the watershed. This condition is characterized by the presence of quite extensive critical land, and also river water pollution due to domestic waste from households, livestock, industry, and agriculture. Analysis of the effect of land cover on water quality show a positive correlation between the increase in settlement area and BOD concentration (r = 0.348–0.692) and TSS, particularly in segment 2 (r = 0.83944). Conversely, DO shows a negative correlation with settlements and plantations (r = -0.51 to -0.92), indicating that urbanization and plantation expansion negatively impact dissolved oxygen levels, while rice fields increase TSS with a correlation value (r = 0.2–0.593). The Driving Force – Pressure – State – Impact – Response (DPSIR) approach highlights the importance of managing green vegetation areas as a key measure in mitigating pollution and improving water quality in the Cilamaya Watershed, as well as in maintaining the overall balance of the ecosystem.